THE IMPACT OF CLIMATE CHANGE ON EDUCATION - Yaqubova Sarvinoz Zafarbek qizi,; Yaqubjonova Ro‘zixon Mirkomil qizi, (TADQIQOTLAR, 2025)
Annotation: This thesis examines the key problems faced in online education and provides possible solutions to overcome them. In particular, factors such as limited access  to  technical  means  and  the  Internet,  lack  of  live  communication  between students  and  teachers,  difficulties  in  self-motivation,  as  well  as  concentration  and effective time management are considered. The study has important theoretical and practical significance for educational systems that are transitioning to online learning.